2018
DOI: 10.4102/ojvr.v85i1.1562
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterisation of African swine fever virus from 2017 outbreaks in Zambia: Identification of p72 genotype II variants in domestic pigs

Abstract: African swine fever (ASF) is a contagious haemorrhagic disease associated with causing heavy economic losses to the swine industry in many African countries. In 2017, Zambia experienced ASF outbreaks in Mbala District (Northern province) and for the first time in Isoka and Chinsali districts (Muchinga province). Meanwhile, another outbreak was observed in Chipata District (Eastern province). Genetic analysis of part of the B646L gene, E183L gene, CP204L gene and the central variable region of the B602L gene of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Malawi and Mbala in Zambia share borders and ASF outbreaks have been reported to temporally coincide (12,26,27).…”
Section: Phylogenetic Reconstruction Of Asfv Targeting B646l (P72) Gementioning
confidence: 99%
“…Malawi and Mbala in Zambia share borders and ASF outbreaks have been reported to temporally coincide (12,26,27).…”
Section: Phylogenetic Reconstruction Of Asfv Targeting B646l (P72) Gementioning
confidence: 99%
“…A total of 15 cases of ASFV with 11 fatalities in pigs were reported in a village. The sequencing and phylogeny confirmed that this outbreak was caused by the ASFV genotype II, which was circulating in the regions of South-Eastern Africa [80]. It was suggested that the genotype II-associated outbreak in Zambia might be due to the import of swine from the neighboring country of Tanzania [79].…”
Section: Zambiamentioning
confidence: 72%
“…The ASFV strain that caused an outbreak in Kyela, Tanzania in 2010 had 100% nucleotide identity for the p72 (B646L) gene to Malawian ASFV collected from the 2011 outbreak in Karonga (Table 1). It was previously speculated that the introduction of ASFV genotype II, previously not described in Tanzania, occurred by importation of pig products from Karonga in Malawi (35,36). Since then, there has been persistent circulation of highly virulent genotype II viruses in the southern highlands of Tanzania, that have devastated nutritional and food security (37).…”
Section: Discussionmentioning
confidence: 99%